Answer:
a = 2
Explanation:
Simplifying
3a + 6 = 2a + 8
Reorder the terms:
6 + 3a = 2a + 8
Reorder the terms:
6 + 3a = 8 + 2a
Solving
6 + 3a = 8 + 2a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-2a' to each side of the equation.
6 + 3a + -2a = 8 + 2a + -2a
Combine like terms: 3a + -2a = 1a
6 + 1a = 8 + 2a + -2a
Combine like terms: 2a + -2a = 0
6 + 1a = 8 + 0
6 + 1a = 8
Add '-6' to each side of the equation.
6 + -6 + 1a = 8 + -6
Combine like terms: 6 + -6 = 0
0 + 1a = 8 + -6
1a = 8 + -6
Combine like terms: 8 + -6 = 2
1a = 2
Divide each side by '1'.
a = 2